2014
DOI: 10.1364/josaa.31.001680
|View full text |Cite
|
Sign up to set email alerts
|

Object-color-signal prediction using wraparound Gaussian metamers

Abstract: Alexander Logvinenko introduced an object-color atlas based on idealized reflectances called rectangular metamers in 2009. For a given color signal, the atlas specifies a unique reflectance that is metameric to it under the given illuminant. The atlas is complete and illuminant invariant, but not possible to implement in practice. He later introduced a parametric representation of the object-color atlas based on smoother "wraparound Gaussian" functions. In this paper, these wraparound Gaussians are used in pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…basing hue on the peak wavelength of a metameric Gaussian-like reflectance from Logvinenko's pseudo-color atlas as the representation of hue. Such Gaussian-like reflectances have been used previously as a tool for predicting how a color signal (i.e., cone response triple) changes with a change in illumination [7]. Similar, but somewhat different, Gaussian-based representations of hue have been proposed previously by Mizokami et al [8][9] and further explored by O'Neil et al [10] and shown to explain the class of hue shifts known as the Abney effect.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…basing hue on the peak wavelength of a metameric Gaussian-like reflectance from Logvinenko's pseudo-color atlas as the representation of hue. Such Gaussian-like reflectances have been used previously as a tool for predicting how a color signal (i.e., cone response triple) changes with a change in illumination [7]. Similar, but somewhat different, Gaussian-based representations of hue have been proposed previously by Mizokami et al [8][9] and further explored by O'Neil et al [10] and shown to explain the class of hue shifts known as the Abney effect.…”
Section: Introductionmentioning
confidence: 87%
“…For the wraparound Gaussian, however, there is no such overlap (see Fig. 2(c) of [7]). The overlap for the subtractive Gaussians implies that for a given XYZ we might find metameric Gaussians of both type G + and G -.…”
Section: Comparison To Other Gaussian-like Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Closure under addition allows us to describe the summation effect of several lighting sources correctly, and closure under multiplication allows us to describe multiple reflections of light from surfaces [16,17] and to approximate high-saturation spectra higher accuracy [14]. Also, an important property is the color set coverage [14,18,19]. As a rule, it is not always possible to satisfy all the properties simultaneously, so the question arises: "How many (and which) properties can a single model have?…”
Section: Introductionmentioning
confidence: 99%